2014
DOI: 10.1152/ajpregu.00302.2012
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of long-term renal sympathetic nerve activity inhibition during an increase in sodium intake

Abstract: It is well known that renal nerves directly affect renal vascular resistance, tubular sodium reabsorption, and renin secretion. Inhibition of renal sympathetic nerve activity (RSNA) decreases renal vascular resistance, tubular sodium reabsorption, and renin secretion, leading to an increase in sodium excretion. Although several studies show that inhibition of RSNA promotes sodium excretion during an acute blood volume expansion, there is limited research relating to the importance of RSNA inhibition that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The "whole-body" mathematical model of blood volume regulation established by Guyton et al incorporated circulatory dynamics, neurohormonal controls, blood fluid controls, and renal function, and demonstrated the physiological compensation that occurs when one part of the entire system is functioning abnormally [28]. Multiple updates, revisions, and improvements have been made to this model over the decades [29][30][31][32][33][34], and have been applied to investigate effects of therapies such as RAAS blockers (e.g. angiotensin-converting-enzyme inhibitor (ACEi)) and SGLT2i on blood pressure, renal hemodynamics, and body fluid regulation [29,35], and the mechanism of pressure natriuresis [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "whole-body" mathematical model of blood volume regulation established by Guyton et al incorporated circulatory dynamics, neurohormonal controls, blood fluid controls, and renal function, and demonstrated the physiological compensation that occurs when one part of the entire system is functioning abnormally [28]. Multiple updates, revisions, and improvements have been made to this model over the decades [29][30][31][32][33][34], and have been applied to investigate effects of therapies such as RAAS blockers (e.g. angiotensin-converting-enzyme inhibitor (ACEi)) and SGLT2i on blood pressure, renal hemodynamics, and body fluid regulation [29,35], and the mechanism of pressure natriuresis [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…angiotensin-converting-enzyme inhibitor (ACEi)) and SGLT2i on blood pressure, renal hemodynamics, and body fluid regulation [29,35], and the mechanism of pressure natriuresis [36,37]. Nevertheless, the simplified representation of cardiac physiology utilized by these mathematical models [31,32,35] has limited the ability to investigate the impact of impaired cardiac function on renal function and body fluid regulation, or the impact of renally or neurohormonally-driven changes in cardiac preload and afterload on cardiac function and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“… 2008 ) and recent models focused on the kidney itself (Karaaslan et al. 2005 , 2014 ; Moss et al. 2009 ; Moss and Thomas 2014 ) or on the role of the kidney in blood pressure regulation (Averina et al.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this paper was to explore the role of renal sympathetic nerve activity (RNSA) on long-term sodium excretion. A later paper suggest that these authors too experienced a light-at-the-end-of-the-tunnel experience when they showed that 'no difference in renal sodium excretion could be observed between intact-and fixed RNSA conditions', perhaps forgetting briefly that, in the long-term, the real or virtual patient has to be in sodium balance, whether or not their renal sympathetic nerve supply is intact (Karaaslan et al, 2014). The later paper allowed for two separate kidneys to be separately innervated or not (plus some further sophistication), and thus provided a fine left-versus-right comparison of the individual renal sodium fluxes resulting from an eight-fold step increase in sodium intake over 5 days.…”
Section: Huge Kidney Models Have Not Led To Consensusmentioning
confidence: 99%